2011
DOI: 10.1016/j.transproceed.2010.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions in Living Kidney Donation: What Protagonists Think and Feel

Abstract: Background. Although donor perceptions of donation have been evaluated in several programs, evaluation of associated recipients has not been as frequent. Purpose. Our aim was to evaluate and compare after transplantation, donor and recipient perceptions of donation. Methods. After transplantation 35 recipients and 45 donors completed a sociodemographic and a donation perception questionnaire. We applied the Fisher test to descriptive (absolute and relative frequency) data. Results. 57.8% of donors were female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The remainder of the LKD questions showed that the majority of participants felt positively about LKD; however, again these were not associated with significant improvements in the psychosocial questionnaire scores. The rate of regret at both 3 and 12 months is in keeping with rates reported elsewhere (0–17%) . Previously documented risk factors for regret, such as graft loss and complications, were not elicited from this study, most likely due to the small numbers of participants expressing evidence of regret and the small number of deaths and graft losses.…”
Section: Discussionsupporting
confidence: 88%
“…The remainder of the LKD questions showed that the majority of participants felt positively about LKD; however, again these were not associated with significant improvements in the psychosocial questionnaire scores. The rate of regret at both 3 and 12 months is in keeping with rates reported elsewhere (0–17%) . Previously documented risk factors for regret, such as graft loss and complications, were not elicited from this study, most likely due to the small numbers of participants expressing evidence of regret and the small number of deaths and graft losses.…”
Section: Discussionsupporting
confidence: 88%
“…; Frade et al . ). A majority of donors would definitively or probably make the same choice if asked and faced with the decision with the benefit of hindsight (Frade et al .…”
Section: Introductionmentioning
confidence: 97%
“…A majority of donors would definitively or probably make the same choice if asked and faced with the decision with the benefit of hindsight (Frade et al . , ). There are positive adjustments in donors characterised by a new appreciation in life, personal growth and improved self‐esteem, in the sense of having contributed to a better life for another person (Ummel et al .…”
Section: Introductionmentioning
confidence: 99%
“…Gordon studied 79 participants over 18 months, finding that only twenty-two percent (n=17) of her sample would ask someone to donate and that, where participants had received offers of a kidney and were pro-transplant (n=23), only one third of this group (n=7) would have asked someone to donate. Participants in Gordon's research drew attention to the difference between asking someone to donate versus accepting an offer of a kidney, and this finding is raised in many studies (Frade et al, 2011;Kranenburg et al, 2009;Waterman, Barrett & Stanley, 2008). Gordon's participants raised two major issues: "(1) asking people to donate is difficult to do, and (2) asking people makes them feel obligated to donate, which is not good because organ donation should be voluntary" (p. 259).…”
Section: Difficulty With Asking or Accepting Offersmentioning
confidence: 99%